Hypertension during pregnancy and risk of stillbirth: challenges in a developing country. (2nd December 2021) - Kumar, Manisha; Singh, Abha; Garg, Rashi; Goel, Manish; Ravi, V.
Abstract: Objective: To explore the factors associated with hypertensive disorders of pregnancy (HDP) in women experiencing stillbirth (SB). Material and methods: It was an observational, analytical case-control study, done as part of the World Health Organization South-East Asian Region Office SB project. The epidemiological profile, history, clinical features, and investigations of stillborn cases having HDP were noted, an equal number of age and parity matched subjects with HDP having livebirth were taken as controls. Results: Out of 46, 816 deliveries, 1239 (26.2/1000) were stillborn. The maternal causes contributed 374/1239 (30.2%) stillbirths according to the CODAC classification, HDP was the most common maternal cause (304/1239, 24.9%). Subjects with HDP were included as cases. On comparing the cases with controls it was found that significantly more number of cases had inadequate antenatal visits ( p  < .001, OR −4.8), two or more abortions ( p  < .001, OR −1.9), early onset of hypertension ( p  < .0001, OR −5.6) and complications such as fetal growth restriction (FGR) ( p  < .001, OR −2.3) and abruption ( p  < .001, OR −4.0). Women with preeclampsia were less likely to have SB compared to those with gestational or chronic hypertension ( p  = .0001, OR −2.3). The birth weight/placental weight ratio of more than eight had the highest odds ratio regarding contribution to SB among hypertensive women ( p  = .0001 OR −6.7). Conclusion: In women with HDP, adequate antenatal care would lead to the prevention of complications such as anemia, abruption, and FGR, and thus prevent SB. The high BW/PW ratio is a potential marker of risk of SB.